Mercy - Baldacci, David (New York : GCP, 2021)
"The #1 New York Times bestselling author with 150 million copies sold worldwide returns with his next blockbuster thriller featuring FBI Agent Atlee Pine"--
Keywords: United States. -- Federal Bureau of Investigation -- Officials and employees -- Fiction; Missing persons -- Fiction; Twin sisters -- Fiction; Family secrets -- Fiction; Thrillers (Fiction); Novels